DNA‐PKcs Deficiency Inhibits Glioblastoma Cell‐Derived Angiogenesis After Ionizing Radiation. Issue 5 (May 2015) - Liu, Yang; Zhang, Luwei; Liu, Yuanyuan; Sun, Chao; Zhang, Hong; Miao, Guoying; Di, Cui Xia; Zhou, Xin; Zhou, Rong; Wang, Zhenhua
<x xml:space="preserve">Abstract</x> DNA‐dependent protein kinase catalytic subunit (DNA‐PKcs) plays a critical role in non‐homologous end‐joining repair of DNA double‐strand breaks (DSB) induced by ionizing radiation (IR). Little is known, however, regarding the relationship between DNA‐PKcs and IR‐induced angiogenesis; thus, in this study we aimed to further elucidate this relationship. Our findings revealed that lack of DNA‐PKcs expression or activity sensitized glioma cells to radiation due to the defective DNA DSB repairs and inhibition of phosphorylated AktSer473. Moreover, DNA‐PKcs deficiency apparently mitigated IR‐induced migration, invasion and tube formation of human microvascular endothelial cell (HMEC‐1) in conditioned media derived from irradiated DNA‐PKcs mutant M059J glioma cells or M059K glioma cells that have inhibited DNA‐PKcs kinase activity due to the specific inhibitor NU7026 or siRNA knockdown. Moreover, IR‐elevated vascular endothelial growth factor (VEGF) secretion was abrogated by DNA‐PKcs suppression. Supplemental VEGF antibody to irradiated‐conditioned media was negated enhanced cell motility with a concomitant decrease in phosphorylation of the FAKTry925 and SrcTry416. Furthermore, DNA‐PKcs suppression was markedly abrogated in IR‐induced transcription factor hypoxia inducible factor‐1α (HIF‐1α) accumulation, which is related to activation of VEGF transcription. These findings, taken together, demonstrate that depletion of DNA‐PKcs in glioblastoma cells at least partly suppressed IR‐inflicted migration, invasion, and tube formation of HMEC‐1 cells, which may be associated with the reduced HIF‐1α level and VEGF secretion. Inhibition of DNA‐PKcs may be a promising therapeutic approach to enhance radio‐therapeutic efficacy for glioblastoma by hindering its angiogenesis. J. Cell. Physiol. 230: 1094–1103, 2015. © 2014 Wiley Periodicals, Inc., A Wiley Company